PEMBELAJARAN TARI KREASI ANAK TUNA GRAHITA RINGAN MELALUI PROSES IMITATIF - Dyan Indah Purnama Sari; Anang Sudigdo; Rizka Diah Amalia (Universitas Sarjanawiyata Tamansiswa, 2018)
Abstract : Creation Dance is a cultivation of new dance work made in accordance with the needs of the consumption of the audience and is the result of creative ideas of the choreographer, especially in this study, the created creations dance is the result of the learning of dance art in the PGSD class that is devoted for children with mild mental retardation at SLB Pembina Yogyakarta. This study describes the learning of Creation Dance of Mild Mental Retardation Children through The Imitative Process, This type of research is qualitative descriptive that describes the process ofÂ children creation dance. The data of this research is from the learning of children dance creation through imitative method. According to Sutjihati Somantri, children with mental retardation are children who have below average intellectual ability, whereas children with mild mental reatardation are children who can still do simple work and do it in full. Through this research, it is expected that children with mild mental reatardation can learn creation dance by imitation or imitative method. The source of research data comes from events, places, and behaviors associated with the study. The resource persons are teachers and students with mild mental retardation in SLB Pembina Yogyakarta.